2020
DOI: 10.3389/fphar.2020.01068
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Uses, Chemical Constituents, Biological Properties, Clinical Settings, and Toxicities of Abelmoschus manihot L.: A Comprehensive Review

Abstract: Abelmoschus manihot , an annual herbal flowering plant, is widely distributed throughout eastern Europe and in temperate and subtropical regions of Asia. Its flowers have been traditionally used for the treatment of chronic kidney disease in China. Currently, more than 128 phytochemical ingredients have been obtained and identified from the flowers, seeds, stems, and leaves of A. manihot . The primary components are flavonoids, amino acids, nucleosides, polysaccharides, organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 102 publications
0
33
0
1
Order By: Relevance
“…Previous studies have shown that TFA has a wide range of pharmacological effects, including anti-inflammatory, analgesic, antioxidant, liver protection, kidney protection, and cardiovascular protection [17,30,[41][42][43][44]. However, TFA has not been systematically studied to verify its activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that TFA has a wide range of pharmacological effects, including anti-inflammatory, analgesic, antioxidant, liver protection, kidney protection, and cardiovascular protection [17,30,[41][42][43][44]. However, TFA has not been systematically studied to verify its activity.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxybenzoic acid derivatives have been detected in the edible flowers of various species, such as Bougainvillea glabra Choisy [38], Abelmoschus manihot (L.) Medik. [39]. While hydroxycinnamic acid has been reported in inflorescences of Butea monosperma (Lam.)…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…: Hibiscus manihot ), commonly called Huang Shu Kui Hua, belongs to the Malvaceae family and is an annual or perennial herbaceous flowering plant and an edible form of hibiscus. 10 Modern pharmacological findings have shown that extracts of A. manihot possess various biological properties, including the ability to treat liver disease, 11 type II diabetic nephropathy, 12 chronic kidney disease, 13 as well as possessing antiproteinuric, 14 anticonvulsant, 15 antidepressant, 15 antioxidative, 16 and pro-angiogenic activity. 17 Numerous studies have demonstrated that the composition of A. manihot flower extracts is very complex, mainly including amino acids, 18 nucleosides, 19 polysaccharides, 20 organic acids, 21 flavonoids, 21 and fatty acids.…”
Section: Introductionmentioning
confidence: 99%